Reproductive Health of Women Veterans: A Systematic Review of the Literature from 2008 to 2017 - Katon, Jodie G.; Zephyrin, Laurie; Meoli, Anne; Hulugalle, Avanthi; Bosch, Jeane; Callegari, Lisa; Galvan, Ileana V.; Gray, Kristen E.; Haeger, Kristin O.; Hoffmire, Claire; Levis, Silvina; Ma, Erica W.; Mccabe, Jennifer E.; Nillni, Yael I.; Pineles, Suzanne L.; Reddy, Shivani M.; Savitz, David A.; Shaw, Jonathan G.; Patton, Elizabeth W. (Seminars in Reproductive Medicine, 2018)
The literature on the reproductive health and healthcare of women Veterans has increased dramatically, though there are important gaps. This article aims to synthesize recent literature on reproductive health and healthcare of women Veterans. We updated a literature search to identify manuscripts published between 2008 and July 1, 2017. We excluded studies that were not original research, only included active-duty women, or had few women Veterans in their sample. Manuscripts were reviewed using a standardized abstraction form. We identified 52 manuscripts. Nearly half (48%) of the new manuscripts addressed contraception and preconception care (n = 15) or pregnancy (n = 10). The pregnancy and family planning literature showed that (1) contraceptive use and unintended pregnancy among women Veterans using VA healthcare is similar to that of the general population; (2) demand for VA maternity care is increasing; and (3) women Veterans using VA maternity care are a high-risk population for adverse pregnancy outcomes. A recurrent finding across topics was that history of lifetime sexual assault and mental health conditions were highly prevalent among women Veterans and associated with a wide variety of adverse reproductive health outcomes across the life course. The literature on women Veterans' reproductive health is rapidly expanding, but remains largely observational. Knowledge gaps persist in the areas of sexually transmitted infections, infertility, and menopause.
Keywords: women Veterans; reproductive health; health services; deployment; women's health